The new China virus - Human Metapneumovirus, its infectivity and rapid spreadis it a threat? - Mulazim Hussain Bukhari, (Journal of the Pakistan Medical Association, 2025)
Human Metapneumovirus (HMPV) causes a highly infectious respiratory disease for all ages and is part of the Pneumoviridae family, but causes diseases for respiratory, milder to most severe; from pneumonia, to bronchiolitis, up to COPD. The virus is pleomorphic in shape and size, varying between 150 nm to 600 nm but very contagious and easily spread by droplets via coughing or sneezing. Children are more at risk giving it a name of kid’s virus. People with a weak immune system as those with heart or lung diseases are also easy victims. The symptoms of HMPV include runny nose, nasal congestion, cough, and fever. HMPV is also known to cause pneumonia. The incubation period is estimated to be 3-6 days with most cases lasting two to five days and then resolving on their own. At times, more severe respiratory symptoms appear as pneumonia requiring hospitalization. The treatment is symptomatic and includes antihistamines, fever reducers, and broncodilators. Keywords: HMPV, Human, Metapneumovirus, Pneumonia, Paramyxoviridae, Pneumovirinae, Pneumoviridae.